The Changing Power Distribution in the South China Sea: Implications for Conflict Management and Avoidance - Ralf, Emmers (2016)
The South China Sea disputes continue to play a destabilizing role in regional security and to act as an irritant in bilateral and multilateral relations. The Paracel and Spratly Islands are at the center of competing territorial, economic and strategic interests. This paper focuses specifically on the changing distribution of power in the South China Sea and assesses its implications for conflict management and avoidance. It notes a growing asymmetry of naval power to the advantage of China, causing concern in some Southeast Asian capitals. The paper discusses how the Southeast Asian nations have traditionally sought to mitigate the unequal power distribution in the South China Sea through a particular model of conflict management and avoidance. While acknowledging its positive impact, the paper highlights the limits of this model in the current context of rising power asymmetry and the swelling security dilemma caused by China’s growing naval strength.